La Chine à la conquête des ressources minières du Canada et de l’Arctique canadien ? Géographie de l’approvisionnement chinois dans le secteur du fer et de l’acier - Pierre-Louis Têtu; Éric Mottet; Frédéric Lasserre (Cybergeo, 2015)
Driven by rapid economic growth, China’s demand for iron ore has significantly increased over the past thirty years. The rise of the Chinese economy, China’s political statement at the world stage, and its diplomatic resources strategy perceived as aggressive, contributed to develop a negative perception of China among the population of Canada. Does China, through its companies, wants to get its hands on the mineral resources of the Canadian Arctic? This article aims to determine the importance of Canada's Arctic territory for Chinese companies in the iron and steel sector, in their global iron ore supply strategies.